2015
DOI: 10.1007/s00784-015-1440-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of material surface on the scanning error of a powder-free 3D measuring system

Abstract: OBJECTIVES This study aims to evaluate the accuracy of a powder-free three-dimensional (3D) measuring system (CEREC Omnicam, Sirona), when scanning the surface of a material at different angles. Additionally, the influence of water was investigated. MATERIALS AND METHODS Nine different materials were combined with human tooth surface (enamel) to create n = 27 specimens. These materials were: Controls (InCoris TZI and Cerec Guide Bloc), ceramics (Vitablocs® Mark II and IPS Empress CAD), metals (gold and amalgam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 24 publications
2
74
0
5
Order By: Relevance
“…21,22 Shiny, rough, undercut, sharp surfaces are known to scan difficult and the saliva is known to create reflective surfaces. 16,35 Additionally, the areas between implants in edentulous arches are large and homogeneous that is difficult to scan accurately. 31,32 Gimenez et al also reported that reference points might lack for correct image stitching in flat mucosal surfaces when combined with a larger interimplant distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Shiny, rough, undercut, sharp surfaces are known to scan difficult and the saliva is known to create reflective surfaces. 16,35 Additionally, the areas between implants in edentulous arches are large and homogeneous that is difficult to scan accurately. 31,32 Gimenez et al also reported that reference points might lack for correct image stitching in flat mucosal surfaces when combined with a larger interimplant distance.…”
Section: Resultsmentioning
confidence: 99%
“…The patients have various hard and soft tissue textures with different reflective surfaces, have variations along the dental arch and anatomic irregularities are absent in the edentulous area to be scanned . Shiny, rough, undercut, sharp surfaces are known to scan difficult and the saliva is known to create reflective surfaces . Additionally, the areas between implants in edentulous arches are large and homogeneous that is difficult to scan accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of saliva on the teeth and the presence of various kinds of brackets is one of the intraoral conditions that may have direct impact on the accuracy of the scanned image [16,17]. ere was a study on the effect of water on the surface of dental restorative materials [18]. Design of the study, however, was only about the effect of reflection of water film on the material margin imbedded in a single tooth.…”
Section: Introductionmentioning
confidence: 99%
“…Direct digitization by means of digital intraoral impressions allows real‐time visualization, enables easy and selective rescanning by the use of a “cut and paste” tool, enables clinicians to check for a possible undercut that may hinder the fabrication of definitive restorations, eliminates the storage space needed for dental casts, and reduces patient discomfort . However, using the method involves a learning curve, and accuracy worsens in the presence of metal restorations and in situations with subgingival margins . Accurate digitization of impressions to create virtual dental casts can also be used to create well‐adapted, long‐lasting dental restorations when using methods that do not involve direct digitization .…”
mentioning
confidence: 99%
“…15,21,22 However, using the method involves a learning curve, and accuracy worsens in the presence of metal restorations and in situations with subgingival margins. 23,24 Accurate digitization of impressions to create virtual dental casts can also be used to create well-adapted, long-lasting dental restorations when using methods that do not involve direct digitization. 2,25,26 The final impression is made with conventional elastomeric impression materials, and the definitive cast fabricated from the impression or the impression itself is scanned with tabletop scanners; these methods are referred to as indirect digitization.…”
mentioning
confidence: 99%